In memoriam of Professor Tadeusz Wolski - Rakowska , M. (Plant Breeding and Seed Science, 2005)
Professor Tadeusz Wolski passed away on March 11, 2005 in age of 81. He is a great person in the history of plant breeding in Poland. In the text below we recall Professor Tadeusz Wolski’s work and achievements as our homage to him.